Biochemical Characterization of Ketapang Lipase: Its Preference to Short-Chain Fatty Acids despite the Long-Chain Fatty Acids Dominant Content - Faradis, Taritsu Hazal; Pomeistia, Meilynda; Basri, Nurul Hasan; 'Ardhuha, Jannatin; Gunawan, Erin Ryantin; Savalas, Lalu Rudyat Telly (Universitas Jenderal Soedirman, 2023)
Lipases are versatile enzymes with high specificity toward lipid substrate. They have many industrial applications, such as in food, pharmacy, and green fuel. So far, most explored lipases are from microbial and animal sources, whereas those from plants are less studied. The present study aims to characterize ketapang (Terminalia catappa Linn) lipase. The lipase was isolated from germinating ketapang seeds. The activity was determined by hydrolysis of virgin coconut oil (VCO). Biochemical characterization of ketapang lipase includes the optimum temperature, pH, kinetics, metal ions addition, and analysis of substrate specificity. It was shown that ketapang lipase has an optimum temperature of 45 oC, pH 7.5. Ca2+ increases the lipase activity, whereas Na+, K+, Mg2+, Zn2+, Fe2+, and Cu2+ inhibit ketapang lipase to various extents. A comparison of SDS-PAGE and native-PAGE analysis showed that ketapang lipase consists of several protein subunits. A further test by in-gel assay revealed that the 54 kDa, 35 kDa, two bands at 16 kDa, and 12 kDa proteins showed lipolytic activity against a-naphthyl palmitate substrate. When tested on various chromogenic fatty acid substrates, ketapang lipase showed the highest specificity against short-chain fatty acids (C4 and C8), despite the fact that ketapang oil seed composes mainly of long fatty acid (C18). Since lipases that have high lipolytic activity toward short fatty acids are considered esterases, the esterase activity of ketapang lipase is yet to be determined.